Histological and Ultrastructural Studies on the Myoid Cells, Macrophages and Melanocytes in the Thymus of Kadaknath Fowl - Panwar, V.S. (Indian Journal of Veterinary Anatomy, 2020)
The Kadaknath breed of poultry is popular far its adaptability and good-tasty grayish black meat, which is believed to infuse vigor. Demand of Kadaknath meat is high due to its contents; high protein and very low fat and cholesterol level. The lymphoid tissue plays an important role in thedefense against all pathogens. The thymus is a primary lymphoid organ which is the first of the lymphoid organs formed and grows immediately after birth in response to postnatal antigen stimulation and demand for large numbers of mature T cells. Histological and Transmission Electron Microscopic studies were conducted on the myoid cells, macrophages and melanocytes found in the thymus of Kadaknath fowls at different age groups. There were three types of myoid cells mainly in the medullaof the gland. Myoid cells may be responsible for contractile activity of the glands causing release of more thymocytes for defense mechanism. Presence of melanocytes in thymus was unique characteristic feature of present study. Melanocytes had round or spindle shaped nuclei and clear cytoplasm with brown pigment granules and many cytoplasmic processes. The numbers of myoid cells, macrophages and melanocytes were increasing with the advancement of age.